Fenomena Musik Ring Back Tone (RBT): Kapitalisme, Budaya Popular, dan Gaya Hidup - Minawati, Rosta (PANGGUNG, 2016)
ABSTRACTÃÂ RBT music is a phenomenon enjoyed by millions ÃÂ of fans. ÃÂ RBT, better known as ring back tones ÃÂ have become part of the lifestyle ÃÂ of subscribers. ÃÂ Ring back tones have sound meanings ÃÂ (as music) which are experienced by callers after placing their calls. The music is heard by callers till the phone is answered. ÃÂ The phenomena of RBT is capable of gaining ÃÂ the interest ÃÂ of a million customers. In Indonesia ÃÂ cellphone use has become widespread, cheap and available. ÃÂ The ÃÂ func- tion ÃÂ of theÃÂ  cellular ÃÂ telephone can facilitate ÃÂ the acquisition ÃÂ of needs for its owner. In general urban centers around the world will form social ÃÂ networks, ÃÂ engage in capitalism, ÃÂ popular cul- ture ÃÂ and life styles. The ÃÂ development ÃÂ of this phenomenon is inseparable from capitalism ÃÂ itself. Through RBT consumers can easily ÃÂ download their favorite songs. In the context ÃÂ of this phe- nomenon capitalism, ÃÂ pop culture ÃÂ and lifestyle represent three inseparable interrelated ÃÂ elements.ÃÂ Keywords: Music RBT, Capitalisme, CulturalPopular, ÃÂ Lifestyle.ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ABSTRAKÃÂ Musik RBT merupakan fenomena yang digemari berjuta pelanggan. RBT atau yang lebih dikenal denganÃÂ ÃÂ  nada sambung menjadi gaya hidup para pelanggannya. Nada sambung (ring back tone) memiliki arti suara (musik) yang di dengar lewat jalur telepon oleh pihak penelepon setelah melakukan pemanggilan. Musik tersebut dapat di dengar pihak yang menghubungi sampai telepon dijawab.Fenomena RBT mampu meraih berjuta pelanggan. Di Indonesia, pengguna Hp menjadi sangat umum, murah dan terjangkau. Fungsi telepon seluler akan lebih memfasilitasi pemenuhan kebutuhan pemiliknya. Secara umum, kota-kota urban di dunia akan membentuk jaringan sosial, kapitalisme, budaya popular, dan gaya hidup. Perkembagan fenomena ini tidak terlepas karena adanya kapitalisme.Melalui RBT, para konsumen dengan mudah mendownloadlagu-lagu yang digemari. Berkaitan dengan fenomena tersebut, kapitalisme, budaya pop(ular) dan gaya hidup merupakan tiga serangkai yang tidak dapat dipisahkan.ÃÂ Kata kunci: Kapitalisme, Budaya Populer, Gaya Hidup